The Economic Thought of Juan de Mariana - Chafuen, Alejandro Antonio (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2014)
The author argues that the period of late scholasticism or post-scholastic produced very important contributions to the analysis of social issues, especially in Economics, Politics and Law. He also highlights Juan de Mariana as one of the most important figures of this period whose legacy in the field of inflation and other theoretical matters is extremely modern.